THE ROLE OF VERIFICATION IN COMPUTER MODELLING: A CASE STUDY IN SOLIDIFICATION PROCESSING - MCFADDEN, SHAUN (My University, 2014)
Computer modelling has become an important aspect of engineering science and technology. Bespoke computer models are routinely under development and are often applied to specific manufacturing and materials processes. Solidification processing (casting for example) is no exception and significant numbers of modelling approaches for solidification are available in literature. The roles of verification and validation in model development for any physical process ought to be clear, but owing to practicalities, it can be difficult to fully verify or fully validate a computer model to a specific requirement. Hence, the terms verification and validation are routinely interchanged or are misconstrued to mean the same thing. This paper outlines a verification study for a Bridgman Furnace Front Tracking Model (BFFTM) of solidification. A formal order verification procedure was applied which showed that the prediction from the computer model converged, in agreement, with an analytical model of the same process. Hence, verification of the BFFTM was achieved
proceeding of the 31st International Manufacturing Conference
PUBLISHED
Cork Institute of Technology
Keywords: solidification; verification; modelling; Mechanical Engineering